Pengaruh Digital Payment (OVO, GoPay, Dana) terhadap Minat Beli Mahasiswa di Marketplace - Inayah Ranitya; Hezra Naumi Syariah Panjaitan; Hopkyn Dwiagstri Domisthira Lumbanbatu (Dinamika Publik: Jurnal Manajemen dan Administrasi Bisnis, 2025)
Along with technological developments, Indonesia is experiencing a transformation in its payment system through the presence of Financial Technology (Fintech), particularly digital payments. Digital payment services such as OVO, GoPay, and Dana are increasingly used by students for transactions in marketplaces because they offer convenience, speed, and security. This study aims to analyze the influence of the use of digital payments OVO, GoPay, and Dana on students' purchasing interest in marketplaces. The variables studied include ease of use, service quality, and promotions offered by digital payment providers. The research method used a quantitative approach with data collection techniques through questionnaires distributed to student marketplace users. Data were analyzed using regression analysis to determine the effect of each variable on purchasing interest. The results of this study are expected to provide an overview of the role of digital payments in encouraging student purchasing interest and serve as a reference for service providers and marketplace players in improving their digital service and promotion strategies.